Basic Income in the Finnish Context - Olli Kangas; Miska Simanainen; Pertti Honkanen (Intereconomics, 2017)
The goal of the Finnish experiment that started this year is to try to get some evidence on how a new social policy instrument mimicking a basic income would work and what kind of behavioural consequences it would have. At this point, there are many strong arguments being made both in favour of and opposed to basic income. Unfortunately, there are not enough facts yet. The Finnish experiment hopes to change that.
Keywords: 330